2017
DOI: 10.18203/2320-1770.ijrcog20171544
|View full text |Cite
|
Sign up to set email alerts
|

Study to assess knowledge, attitude and practice regarding menopause among menopausal women attending outdoor in tertiary care centre

Abstract: Background: India is a developing country and it is growing rapidly in all aspects of life. Health status of population has improved and hence the life expectancy. Women are affected positively by this improvement and their life expectancy has become longer than men. Women all over the world now have to spend almost 1/3rd of their lives in menopausal years. Therefore, menopause now is a concerning matter to maintain and improve women's health. Methods: This analytical study was conducted for a period of 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 6 publications
7
20
2
Order By: Relevance
“…In this study maximum (61.6%) of participants were attained their menopause in the age between 45-50 years, which was similar to a study conducted by Nahid Yasmin et al that majority of the respondents (63.5%) were the age between 45-50 years (Yasmin et al, 2009). Majority (76.9%) were literate in the present study in contrast to another study (Pathak et al, 2017), where, 55.45% of participants were illiterate. Most of the participants (90.4%) belonged to middle class socioeconomic background.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In this study maximum (61.6%) of participants were attained their menopause in the age between 45-50 years, which was similar to a study conducted by Nahid Yasmin et al that majority of the respondents (63.5%) were the age between 45-50 years (Yasmin et al, 2009). Majority (76.9%) were literate in the present study in contrast to another study (Pathak et al, 2017), where, 55.45% of participants were illiterate. Most of the participants (90.4%) belonged to middle class socioeconomic background.…”
Section: Discussioncontrasting
confidence: 92%
“…In the current study, 44.2% of women considered postmenopausal bleeding as abnormal, but in the study by Pathak et al,16.3% women considered postmenopausal bleeding as abnormal (Pathak et al, 2017). Other studies reported that majority participants had knowledge about that menopause is associated with many chronic diseases like cancer, osteoporosis etc., (Pathak et al, 2017) (Thomas, 2005. In our study we also found that 36.5% respondents were aware about it.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Further analysis is needed to adjust for age. our results regarding knowledge about HrT and its use to alleviate menopausal symptoms are consistent with those of previous studies [45][46][47]. in addition to women's lack of knowledge about HrT use, it seems that underuse of hormonal therapy could be due to physicians' hesitance to prescribe these medications despite current recommendations that favour the use of HrT for patients younger than 60 with no contraindications [48].…”
Section: Factors Affecting Menopausal Agesupporting
confidence: 90%